From Asia, with Skills. - Khanna, Gaurav (Journal of Economic Perspectives)
This paper examines the rise of high-skill migration from Asia to the United States since 1990 and its consequences for sending and receiving economies. Over 1990–2019, migrants from India, China, South Korea, Japan, and the Philippines accounted for over one-third of US growth in software developers and a quarter of the increase in scientists, engineers, and physicians. Using census microdata, visa records, and administrative sources, I show how growing US demand for talent in information technology, higher education, and healthcare interacted with Asia's demographic and educational transformations. Policy reforms in the H-1B, F-1, and J-1 programs and sectoral shifts—such as the internet revolution and aging-related healthcare demand—generated persistent needs for foreign students and workers. Asian economies were uniquely positioned to meet this demand through tertiary expansion, strong STEM institutions, English proficiency, and diaspora networks. These inflows boosted US innovation while fostering "brain gain" and "brain circulation" in Asia.